A Danish national, multicentre evaluation of the new donor vigilance system among different staff groups. Issue 2 (15th December 2022) - Mikkelsen, Christina; Paarup, Helene Martina; Bruun, Mie Topholm; Pedersen, Louise Ørnskov; Hasslund, Sys; Larsen, Rune; Aagaard, Bitten; Sørensen, Betina Samuelsen
Abstract: Background and Objectives: Two years after implementing a new national donor vigilance system, the Danish Haemovigilance Committee conducted a nationwide survey to evaluate the implementation among different staff groups. We present the results here. Materials and Methods: The study was designed as an anonymous online survey to evaluate the satisfaction with the new registration, understanding of the parameters used and the user‐friendliness. The REDCap platform was used. The questionnaire consisted of 22 questions. Ordinal variables were answered using five‐point Likert scale (1 = strongly disagree to 5 = strongly agree). The data were analysed using descriptive statistics. Successful implementation was defined as mean overall satisfaction ≥4 and mean understanding of the individual components (adverse reaction category, severity and imputability) in the registration ≥4. Results: In all, 104 staff members (77.9% donation staff) participated. The mean (SD) overall satisfaction among all participants was 3.96 (0.94), highest among medical doctors (4.43 (0.78)) and lowest for administrative or other personnel (2.78 (1.09)). The mean scores for understanding the adverse reaction categories, severity and imputability were 3.92 (0.94), 3.92 (0.94) and 3.88 (1.00), respectively. Experience with a previous donor vigilance system was associated with lower scores. The most successful implementation programme included a medical doctor for introduction and a contact person. Conclusion: The goal for successful implementation was not met. However, the overall attitude towards the new registration was positive and indicates that the system is suitable for different staff groups. Our results suggest that implementation could benefit from special attention to administrative staff and those accustomed to another donor vigilance system.